Implementasi Sistem Pemantauan Energi Listrik dan Perbaikan Faktor Daya Berbasis Android dengan MIT App Inventor dan Firebase - Andre Rabiula; Dasrinal Tessal; Aldy Pratama; Togi Siholmarito Simarmata; Elsa Lolita Anggraini; Illa Aryeni (Journal of Applied Electrical Engineering, 2025)
As inductive loads like washing machines and water pumps become more common, they utilize more reactive energy and lower the power factor. If the power factor is less than 0,85 PLN, electrical protection devices like MCBs and ELCBs could stop working. To utilize less power, things need to change. Adding a capacitor bank to add reactive power can make the power factor value better. Using the MIT App Inventor and Firebase platforms, this study built an app that lets you keep track of and improve your power factor. The app had an average data latency of 11,20 seconds. After 11 load changes, the average power factor went up from 0,64 (before improvement) to 0,88 (after). So, this method for optimizing power factor helps to get a low power factor up to the right level.